Zhizhu Kuanzhong, a traditional Chinese medicine, alleviates gastric hypersensitivity and motor dysfunction on a rat model of functional dyspepsia - Xiao, Zhuanglong; Xu, Jing; Tan, Jun; Zhang, Shengyan; Wang, Nian; Wang, Ruiyun; Yang, Pengcheng; Bai, Tao; Song, Jun; Shi, Zhaohong; Lyu, Wenliang; Zhang, Lei; et al. (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Zhizhu Kuanzhong (ZZKZ) is a traditional Chinese medicine modified from the classic formula Zhizhu decoction in “Synopsis of Golden Chamber’’ (Han Dynasty in the 3rd century) and the Zhizhu pill in “Differentiation on Endogenous” (Jin Dynasty in 1232). ZZKZ contains four herbs, including Citrus Aurantium L., Atractylodes Macrocephala Koidz., Crataegus Pinnatifida Bunge, and Bupleurum Chinense DC., which have been widely used in clinical therapy for functional dyspepsia (FD). Aim of the study: This study aimed to evaluate the pharmacological effects and mechanisms of action of ZZKZ on gastric hypersensitivity and motor dysfunction in a rat model of FD. Materials and methods: FD was induced in Sprague-Dawley rats by neonatal gastric irritation with 0.1% iodoacetamide. The FD rats were treated with ZZKZ (0.5 g/kg, 1.0 g/kg, or 1.5 g/kg respectively) by gavage for 7 days, while domperidone (3mg/kg) acted as treatment control. Body weight gain, food intake, gastric emptying, and intestinal propulsion were also measured. Ex vivo gastric smooth muscle activity recordings and greater splanchnic afferent (GSN) firing recordings were employed to evaluate gastric motility and sensation. Particularly, the role of 5-HT in the action of ZZKZ in improving gastric dysmotility and hypersensitivity was explored. Results: ZZKZ promoted weight gain, food intake, gastric emptying, and intestinal propulsion in FD rats. ZZKZ promoted spontaneous and ACh-induced contractions of gastric smooth muscle strips in FD rats, alleviated spontaneous activity, and chemical (acid perfusion) and mechanical (intragastric distension) stimulated GSN firing in FD rats. ZZKZ ameliorated gastric smooth muscle contraction and GSN firing induced by 5-HT in FD rats. ZZKZ stimulated the release of serum 5-HT, with reduced 5-HT3 receptor and increased 5-HT4 receptor mRNA expression in the guts of FD rats. Conclusions: This study demonstrated that ZZKZ improves FD-related gastric hypersensitivity and motor dysfunction and may be an effective compound for relieving FD symptoms. The gastric 5-HT system with lower 5-HT3 activity and increased 5-HT4 distribution may be involved in the mechanisms of ZZKZ underlying the treatment of FD.